Fluconazole-Induced Stevens–Johnson Syndrome in a Type 2 Diabetic Male: A Case Report - ., Maryam; Salma Wajid; Anas Fatima; Ahmed Hasan Mohiuddin (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Stevens–Johnson Syndrome (SJS) is a rare but potentially life-threatening mucocutaneous hypersensitivity reaction, most commonly induced by drugs. Fluconazole, an antifungal agent widely used to treat candidiasis, is infrequently associated with SJS. Case Presentation: We report a case of a 37-year-old male with Type 2 Diabetes Mellitus admitted with multiple oral ulcers, erythematous genital lesions, and excoriation of skin over hands and feet. He had been diagnosed with oral candidiasis and candidal balanitis five days earlier and was on oral Fluconazole 150 mg daily. On admission, the dose was escalated to 200 mg intravenously and subsequently to 250 mg. Within three days, the patient developed crusted erosions over the lips and buccal mucosa, with erythematous erosions over the genitalia, suggestive of SJS. Fluconazole was immediately withdrawn, and systemic corticosteroid therapy was initiated along with supportive care. The patient showed gradual improvement with re-epithelialization and complete recovery over one week. Conclusion: This case highlights the rare occurrence of Fluconazole-induced SJS and underscores the importance of early recognition, prompt withdrawal of the offending drug, and multidisciplinary management to prevent morbidity.